A model and software for the inertial measurement unit - Bezpalko, S.O.; Shymkovysh, V.M.; Doroshenko, A.Yu. (Інститут програмних систем НАН України, 2022)
The module of stabilization of an inclination of the plane with three degrees of freedom, the software for data acquisition from MPU-6050 using the I2C protocol, and the program of realization of the digital proportional-integral-diff erential regulator with algorithm of subtomatic factor is developed. A model of a gyroscopic device for testing the created solution was built. Considering time and resource constraints, the following solutions were chosen: PID controller for motor voltage control, PWM as a way to create a control signal, Kalman fi lter for processing output of the IMU, device and relay method in pairs with the Ziegler-Nichols method for the selection of the coeffi cients of the regulator. Test results or the following characteristics of the transition process: the time of the transition process - 0.44s, overregulation - 6.2%. Further improvement of the quality of the transient process is possible through the use of high- quality inertial measuring devices, high-precision electric motors withhigh torque.Prombles in programming 2022; 2: 03-12